The use of ash and biochar derived oil palm bunch and coal fly ash for improvement of nutrient availability in peat soil of Central Kalimantan - Gusti Irya Ichriani; Yustinus Sulistiyanto; Hastin Ernawati Nur Chusnul Chotimah (Journal of Degraded and Mining Lands Management, 2021)
The increment of peat soil productivity meets through ameliorant addition. Ameliorant sources can be obtained from oil palm plantation and electric steam power station waste. The study aimed at investigating the ability of the oil palm fruit empty bunch (OPFEB) biochar, palm oil boiler ash (POBA) and coal fly ash (CFA) as alternative ameliorants besides compost to improve nutrient availability in peat soil of Central Kalimantan. Treatments tested were OPFEB biochar, POBA, CFA, compost, OPFEB biochar+compost, POBA+compost, and CFA+compost. The seven treatments were arranged in a completely randomized design of single factor with four replications. The results revealed that the ameliorants increased peat soil pH at a rate of 0.7 compared to those in initial soil used and available P of 135.7% even though there was no significant increment of exchangeable cations of K, Ca and Mg. Mixing of biochar, POBA or CFA with compost improved nutrients availability in peat soil.